Antioxidant activity and acute toxicity of ziziphus abyssinica extracts: A comparative study of root and leaf extracts - Tsegay Beyene Weldemariam; Abebaye Aragaw Leminie; Worku Gemechu; Samuel Woldekidan Hirpesa; Getahun Tsegaye Dibaba; Kerat Ali Muhamed; Beza Tasew Degefu; Tesfaye Tolessa Dugul (Toxicology Reports)
Ziziphus abyssinica Hochst. ex A. Rich., a traditionally valued Ethiopian medicinal plant, was investigated for its phytochemical composition, antioxidant potential, and acute toxicity to validate its ethnopharmacological uses. Through sequential solvent extraction (n-hexane to aqueous), methanol and ethyl acetate fractions of leaves exhibited superior antioxidant activity (DPPH EC50: 12.5 ± 0.8 μg/mL; ABTS EC50: 15.2 ± 1.0 μg/mL), correlating with high phenolic (120.5 ± 0.7 mg GAE/g) and flavonoid (85.6 ± 0.6 mg QE/g) content. Leaves consistently outperformed roots across assays, reflecting tissue-specific metabolic specialization. Comprehensive phytochemical profiling revealed alkaloids, saponins, and glycosides, with quantitative analysis demonstrating solvent-dependent metabolite recovery. Acute toxicity testing using Organization for Economic Co-operation and Development (OECD) Guideline 425, at 2000 mg/kg showed no mortality or significant biochemical alterations, though mild hepatic vacuolization was observed histologically. The study highlights Z. abyssinica’s dual promise as a source of natural antioxidants with a favorable safety profile, while establishing standardized protocols for its evaluation. These findings bridge traditional knowledge with scientific validation, supporting its potential development for nutraceutical or therapeutic applications targeting oxidative stress-related pathologies.